(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article emphasizes that preparing young people for family life is one of the most pressing issues. While preparing for family life may seem to be a purely personal matter, unrelated to others, this perspective highlights the factors that protect the development of our nation, the morals of our people, our future, and our lineage from harm.